A town as the common good – social and economic perspective (Economic and Political Thought, 2014)
A town may be considered to create a system of common resources,providing living space, jobs and other factors in life quality for its dwellers.Fair and efficient management of these resources requires a specific type ofmanagement. According to the findings of E. Ostrom et al., the descriptionof the urban system goes beyond the dichotomy between market and publicgoods; and the dichotomy between market mechanisms and the public sectorand their unreliability does not make it possible to provide optimal effects.This mainly results from a specific character of the goods themselves, as wellas a town as a complex system with strong external effects. This applies tothe character of urban land management in particular. The current paperproposes the analysis of urban space as common pool resources (CPR).The barriers and potential failures to implement Ostrom’s theory to urbanmanagement have been presented, as well as the potential for choosing thistheory as an alternative both to commercialization and centralization. Theimportance of the role of local self-government in negotiating, monitoringand supervising the rules of CPR’s use has also been described.